Implementasi Pembelajaran Kolaboratif dalam Pengajaran Menulis Teks Persuasif Berbahasa Inggris untuk Promosi Kuliner MinangKabau - Rosi Kumala Sari; Mona Afersa; Wienda Gusta (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the implementation of collaborative learning in teaching persuasive writing in English for promoting Minangkabau culinary products among Management students in the Business English course at Universitas Putra Indonesia YPTK Padang in the 2025/2026 academic year. This research employed a qualitative approach. The participants consisted of 42 students. Data were collected through classroom observations, analysis of students’ writing assignments, and semi-structured interviews. The findings indicate that the implementation of collaborative learning significantly enhances students’ ability to construct persuasive texts, particularly in terms of idea organization, argument development, the use of business-related vocabulary, grammatical accuracy, and persuasive strategies such as emotional appeal and logical reasoning. In addition, collaborative activities promote increased student participation, self-confidence, and interpersonal communication skills in both academic and business contexts. The integration of local context, specifically the promotion of Minangkabau culinary products, provides a more contextual and meaningful learning experience that is relevant to real-world applications. This study concludes that collaborative learning is an effective approach to improving students’ English persuasive writing skills. Therefore, it is recommended that lecturers integrate collaborative strategies with locally-based cultural content to enhance the quality of English language teaching in higher education.